Satisfaction and Loyalty of Customers towards the Retail Store Formats- Evidence from India - Sreekanth, Prathyusha (2015)
This study aims to identify attributes that contributes to customer satisfaction and loyalty in Indian retail market. Past studies led to the understanding that store attributes, product attributes and service attributes primarily affected the store satisfaction and loyalty of Indian consumers. The findings of this study revealed that only store attributes and product attributes had a profound impact on customers’ loyalty and satisfaction while service attributes did not have any impact. These findings have significant policy implications for the store managers as well as the Government of India.